2010
DOI: 10.1007/s00267-010-9538-7
|View full text |Cite
|
Sign up to set email alerts
|

Thinning Pine Plantations to Reestablish Oak Openings Species in Northwestern Ohio

Abstract: Globally the area in forest plantations is rising by 2% annually, increasing the importance of plantations for production of human goods and services and for ecological functions such as carbon storage and biodiversity conservation. Specifically in the Great Lakes states and provinces of Midwestern North America, thousands of hectares of pine plantations were established in the early and mid-1900s to revegetate abandoned agricultural fields that had replaced mixed-species forests and oak-prairie ecosystems. Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The species usually occurs in abundance and high density in places of recent major disturbance, although small scale disturbances giving rise to suitable microsites are colonized by small numbers of plants. Disturbances may result from fires (Masters et al 1996;Nakagoshi et al 2003;Hutchinson et al 2005), forest cutting (Boring et al 1981;Masters et al 1996;Landenberger and McGraw 2004;Mou et al 2005;Abella 2010), herbicide application (Kochenderfer and Wendel 1983;Luken et al 1994), cultivation ( Fig. 5), flooding or hydrological changes (Shull 1914;Leck et al 1988; herbarium specimen label data), erosion , or other disturbances (Wagner 1966;Hunt and Shure 1980;Roman et al 1984).…”
Section: Habitatmentioning
confidence: 97%
See 1 more Smart Citation
“…The species usually occurs in abundance and high density in places of recent major disturbance, although small scale disturbances giving rise to suitable microsites are colonized by small numbers of plants. Disturbances may result from fires (Masters et al 1996;Nakagoshi et al 2003;Hutchinson et al 2005), forest cutting (Boring et al 1981;Masters et al 1996;Landenberger and McGraw 2004;Mou et al 2005;Abella 2010), herbicide application (Kochenderfer and Wendel 1983;Luken et al 1994), cultivation ( Fig. 5), flooding or hydrological changes (Shull 1914;Leck et al 1988; herbarium specimen label data), erosion , or other disturbances (Wagner 1966;Hunt and Shure 1980;Roman et al 1984).…”
Section: Habitatmentioning
confidence: 97%
“…For example, seeds of E. hieraciifolius have been shown to be short-lived or transitory in mixed-oak hardwood clearings in the southern Appalachians where they are abundant in the early-successional period, but rapidly decline and are replaced by more shade-tolerant species with the growth of over-story trees and gradual canopy closure in the late-successional period (Elliott et al 1997). In managed pine plantations in Ohio, the importance value (sum of relative cover and relative frequency) of E. hieraciifolius was 0.6 in un-thinned control plots and 9.5 in plots 3 yr after thinning (Abella 2010). In a managed pine plantation in South Carolina, Mou et al (2005), found the high importance value of E. hieraciifolius (6.3) attained in the first post-harvest growing season declined rapidly in the following 4 yr (3.8, 0.5, 0, and 0.2, respectively).…”
Section: Population Dynamicsmentioning
confidence: 98%
“…An important question is how to manage them in the future. One of the options is to gradually transform them by thinning into more or less natural forests [11,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…Plantations are often established on abandoned agricultural lands around the world [11]. They have several positive effects [12] and have been the subject of numerous studies [13]. An important question is how to manage them in the future.…”
Section: Introductionmentioning
confidence: 99%
“…We followed the general approach offered by Kumar and others (2006), utilizing field data, remotely sensed data, and landscape pattern metrics to develop multi-scale predictive models of native and exotic plant species richness for remnant savanna, prairie and barrens communities. We chose to focus on these specific communities because they remain a target for ongoing conservation and restoration efforts throughout the Midwestern United States (Leach and Ross 1995; Abella and others 2007; Abella 2010). We examined the following specific research questions within the context of a mixed-disturbance oak savanna landscape: (1) Can we reliably predict native and exotic richness patterns using a subset of selected explanatory variables?…”
Section: Introductionmentioning
confidence: 99%